SUPPORT WITH ADJUSTABLE WIDTH FOR STENCIL PRINTING - CSUFOR, CSABA ZSOLT; FORGÁCS, DÉNES ISTVÁN (2024)
The subject of the invention is a support for stencil printing, with adjustable width. The support has a lower support (2) fixed between a machine table (1) and an upper support (3). The width of the lower support (2) is adjustable using a scissor mechanism to support upper supports (3) of different width. The lower support (2) has means for fixing its bottom to the machine table (1), means for fixing its top to the upper support (3), a means for indicating its width, a means for fastening the scissor mechanism to maintain its width, and a means for detaching the lower support (2) from the machine table (1).